2020
DOI: 10.1088/1361-6528/ab884b
|View full text |Cite
|
Sign up to set email alerts
|

Initial stage of MBE growth of MoSe2 monolayer

Abstract: An atomically thin MoSe2 layer has been synthesized on mica using molecular beam epitaxy (MBE). The polymorphous of the MoSe2 layer depends on the coverage and the growth temperature. At low coverages and low growth temperature, 1T-MoSe2 forms in addition to a comparable quantity of 2H-MoSe2. The metastable 1T-MoSe2 transfers gradually to the stable 2H-MoSe2 before the completion of the first monolayer. The current result sheds some light on the complexity of the nucleation and growth of transition metal dicha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…3(l–o)). 99 Recently, Wei et al 100 have shown the complex nature of the nucleation and growth processes of MoSe 2 monolayers grown via MBE on mica. It has been observed that the 1T phase of MoSe 2 forms along with a comparable quantity of the 2H phase of MoSe 2 , where the 1T phase converts gradually into the stable 2H phase before the complete growth of the first monolayer.…”
Section: Recent Advances In Mbe-grown Transition Metal Dichalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…3(l–o)). 99 Recently, Wei et al 100 have shown the complex nature of the nucleation and growth processes of MoSe 2 monolayers grown via MBE on mica. It has been observed that the 1T phase of MoSe 2 forms along with a comparable quantity of the 2H phase of MoSe 2 , where the 1T phase converts gradually into the stable 2H phase before the complete growth of the first monolayer.…”
Section: Recent Advances In Mbe-grown Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…95 In a recent report, He et al 96 wafer through an in-depth examination of the optical studies (Figure 3(l-o)). 99 Recently, Wei et al 100…”
mentioning
confidence: 99%
“…[5] Moreover, structural imperfection and phase mixing during initial growth stage have also been recently reported for MoS 2 and MoSe 2 layers grown by pulsed laser deposition and MBE on sapphire and mica wafers. [6,7] The defect-rich nature of the first layer seems to be intrinsic for PVD growth of TMCDs at least during heteroepitaxy on substrates with high structural mismatch, making direct fabrication of high-quality monolayers extremely challenging. In contrast, CVD can readily provide large crystalline single monolayer (ML) flakes and continuous layers.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial method like metalorganic vapor phase epitaxy (MOVPE) was also used to address the TMD scalability problem and it has been shown that it is possible to produce wafer-scale materials although so far not with the same optical properties. Molecular beam epitaxy (MBE) appears to be a promising candidate for the development of large-area samples, as it allows the production of high purity materials with atomic precision. However, the optical quality of the samples is still far behind the best results obtained for mechanically exfoliated flakes. A way to overcome this obstacle is to combine TMD layers with hBN.…”
Section: Introductionmentioning
confidence: 99%